2020
DOI: 10.1002/adbi.201900239
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of Virulence Plasmid in Clinical Klebsiella pneumoniae Strains through Formation of a Fusion Plasmid

Abstract: The rapid dissemination of non‐conjugative virulence plasmids among non‐K1/K2 types of Klebsiella pneumoniae poses an unprecedented threat to human health, yet the underlying mechanisms governing dissemination of such plasmids is unclear. In this study, a novel 68 581 bp IncFIA plasmid is discovered that can be fused to a hypervirulence‐encoding plasmid to form a hybrid conjugative virulence plasmid in conjugation experiments; such fusion events involve homologous recombination between a 241 bp homologous regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 33 publications
0
40
0
Order By: Relevance
“…The larger plasmid, pMS3802-CTXM-vir, belonged to the incompatibility group IncHI1B, and it is an example of hybrid resistance/virulence plasmid. Hybrid plasmids containing both drug-resistance and virulence-related genes have been recently described [ 23 , 32 , 33 , 34 , 35 ]. pMS3802-CTXM-vir carried a second copy of the bla CTX-M-15 gene within the same gene arrangement as the one located in the chromosome IS 26 -Tn 3 - wbuC - bla CTX-M-15 -IS Ec9 ( Figure 2 A), indicating that bla CTX-M-15 was acquired as a result of activities of these mobile genetic elements (MGEs).…”
Section: Resultsmentioning
confidence: 99%
“…The larger plasmid, pMS3802-CTXM-vir, belonged to the incompatibility group IncHI1B, and it is an example of hybrid resistance/virulence plasmid. Hybrid plasmids containing both drug-resistance and virulence-related genes have been recently described [ 23 , 32 , 33 , 34 , 35 ]. pMS3802-CTXM-vir carried a second copy of the bla CTX-M-15 gene within the same gene arrangement as the one located in the chromosome IS 26 -Tn 3 - wbuC - bla CTX-M-15 -IS Ec9 ( Figure 2 A), indicating that bla CTX-M-15 was acquired as a result of activities of these mobile genetic elements (MGEs).…”
Section: Resultsmentioning
confidence: 99%
“…discovered such a hybrid plasmid in a clinical Klebsiella variicola strain and confirmed its self-transferable ability [ 15 ]. Another study observed homologous recombination between a virulence plasmid and an IncF1A plasmid in a clinical K. pneumoniae strain, which yielded a conjugative hybrid plasmid [ 16 ]. Li et al .…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, these non-K1/K2 CR-HvKP strains, in particular the ST11 type of CR-HvKP, have quickly spread throughout China and severely undermined infection control effort. Recent studies reported the transmission of non-conjugative virulence plasmid through forming a conjugative fusion plasmid with a conjugative helper plasmid, while there is still lack of direct evidence of transmission of virulence from K1/K2 K. pneumoniae strains 31 , 32 . Our study revealed the process of transmission of the virulence plasmid from K2 HvKP to non-K1/K2 K. pneumoniae , generating non-K1/K2 CR-HvKP.…”
Section: Discussionmentioning
confidence: 99%